Traditional Chinese Medicine Preparation Combined Therapy May Improve Chemotherapy Efficacy: A Systematic Review and Meta-Analysis. (20th June 2019) - Wu, Jiaming; Liu, Yun; Fang, Cantu; Zhao, Lixian; Lin, Lizhu; Lu, Liming
Abstract : Background. Whether traditional Chinese medicine preparation combined therapy can improve the efficacy of chemotherapy is controversial. This meta-analysis evaluates the efficacy of traditional Chinese medicine preparation combined with chemotherapy. Method. Three databases were searched from inception through August 2018. Eligible randomized controlled trials (RCTs) involving the combined treatment of chemotherapy and traditional Chinese medicine preparation compared to chemotherapy alone for treating cancer were retrieved. The methodological quality of the included RCTs was assessed with Cochrane Collaboration's risk of bias assessment tool. Meta-analysis was adopted to make comprehensive comparisons between the experimental and control groups. Results. Four RCTs were included in this review, comprising 256 subjects. The majority of the RCTs were judged as being of poor methodological quality. Meta-analysis showed that the combination of traditional Chinese medicine preparation and chemotherapy appeared to be more effective than chemotherapy alone, for the treatment of cancer, as assessed by the disease control rate (RR: 1.41, 95% CI: 1.11 to 1.79) and the objective response rate (RR: 2.71, 95% CI: 1.28 to 5.77). There were no statistically significant differences between the groups in terms of bone marrow suppression (RR: 0.88, 95% CI: 0.57 to 1.37) or gastrointestinal reaction (RR: 1.12, 95% CI 0.75 to 1.69). Conclusions. Traditional Chinese medicine preparation combined with chemotherapy may improve objective response rates and disease control rates more than chemotherapy alone. The evidence that combined traditional Chinese medicine preparation can reduce the side effects of chemotherapy is insufficient. More rigorous randomized controlled trials are needed to confirm these conclusions.